The Influence of Convenience, Expediency, and Trust on Consumers' Decisions in Using Digital Platforms as A Means of Paying Zakat, Infaq, and Alms - Rizma Adinda; Alvien Nur Amalia (Jurnal Ilmu Manajemen & Ekonomika, 2021)
Advances in technology and information have made zakat, infaq, and alms managers innovate and collabo-rate with various digital platforms in Indonesia which aim to facilitate the distribution of zakat, infaq, and alms (ZIS). This research was conducted to find out and analyze the variables of convenience, expediency, and trust that influence consumers' decisions in using digital platforms to pay zakat, infaq, and alms. The sample used in this study was 155 respondents who were domiciled in the Jakarta, Bogor, Depok, Tange-rang, and Bekasi (Jabodetabek) regions. In the selection of samples, this study used purposive sampling techniques and data processing was carried out using the IBM Version 26.0 Statistical Package for the So-cial Sciens (SPSS) application. The results showed that all independent variables, namely convenience, expediency, and trust have an influence both partially and simultaneously on consumers' decisions to use digital platforms as a means of paying zakat, infaq, and alms. The easier it is to use, the benefits are felt, and consumer trust in digital platforms when paying for ZIS using digital platforms can increase consum-ers' decision to use digital platforms as a means of paying for ZIS.